Gender differences in tertiary education: What explains STEM participation? - Sandra McNally (Institute of Labor Economics (IZA), 2020)
The share of women achieving tertiary education has increased rapidly over time and now exceeds that of men in most OECD countries. However, women are severely underrepresented in maths- intensive science fields, which are generally referred to as STEM (science, technology, engineering, and maths). The under-representation of women in these subject areas has received a great deal of attention. This is because these fields are seen to be especially important for productivity and economic growth and are associated with occupations that have higher earnings. Subject of degree is an important part of the explanation for the gender wage gap. The aim of this paper is to review evidence on explanations for the STEM gap in tertiary education. This starts with statistics about background context and evidence on how well-prepared male and female students may be for studying STEM at a later stage. I then discuss what the literature has to say about the role of personal attributes: namely confidence, self-efficacy and competitiveness and the role of preferences and expectations. I go on to discuss features of the educational context thought to be important for influencing attributes and preferences (or mediating their effects): peers; teachers; role models; and curriculum. I then briefly discuss broader cultural influences. I use the literature reviewed to discuss policy implications.
Keywords: I20; J16; 330; STEM; gender gap; tertiary education